2018
DOI: 10.1016/j.actbio.2018.05.048
|View full text |Cite
|
Sign up to set email alerts
|

Mediating human stem cell behaviour via defined fibrous architectures by melt electrospinning writing

Abstract: This is the first study which has investigated the effect of controlled fibrous architectures fabricated via melt electrospinning writing on stem cell behaviour and differentiation. After optimising the fabrication process and characterising scaffolds via SEM and mechanical testing, skeletal stem cells were seeded onto fibrous scaffolds with various micro-architectures. These architectures drove cell shape changes resulting in architecture dependent nuclear YAP localisation, suggesting altered mechanosensing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
113
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(118 citation statements)
references
References 59 publications
3
113
2
Order By: Relevance
“…Our previous experiments on ADM without laser perforating also confirmed this mechanism (Zhu et al, ). Scaffolds can produce specific microenvironments depending on their morphological, chemical, and mechanical properties, which can influence material‐cell interactions and affect the behavior of seed cells (Eichholz & Hoey, ); (Su et al, ). Our previous studies have found that PADM can provide rADSCs with a microenvironment that facilitates their paracrine function (Zhu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous experiments on ADM without laser perforating also confirmed this mechanism (Zhu et al, ). Scaffolds can produce specific microenvironments depending on their morphological, chemical, and mechanical properties, which can influence material‐cell interactions and affect the behavior of seed cells (Eichholz & Hoey, ); (Su et al, ). Our previous studies have found that PADM can provide rADSCs with a microenvironment that facilitates their paracrine function (Zhu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The phenomena underlying the observed responses are diverse. In some cases cells are directly affected by the physical cues, i.e., via contact guidance, cytoskeletal reorganization or mechanotransduction . This is the case in the responses to strut size and roughness or to attachment to fibers forming different angles at their intersections.…”
Section: Strategies To Evolve From Shape To Functionmentioning
confidence: 99%
“…MSC adhering to 10° laydown patterns were more likely to elongate along the fibers, whereas cells preferentially followed the curvature at the intersection between fibers printed with 90° laydown angles. This conformation resulted in a mechanical stress that induced nuclear translocation of YAP, and eventually improved osteogenic differentiation …”
Section: Strategies To Evolve From Shape To Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, a scaffold with precise architecture and microporous structure was produced by using melt electrospinning technology (Eichholz & Hoey, ) obtaining a 3D mesh with a pore size of 50 μm from a top view perspective. Melt electrospinning technique forms well‐defined filaments with small diameters that can be deposited into 3D architectures using AM principles (Figure ; Brown, Dalton, & Hutmacher, ; Muerza‐Cascante, Haylock, Hutmacher, & Dalton, ).…”
Section: Microporesmentioning
confidence: 99%